2016
DOI: 10.1186/s12933-016-0404-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic syndrome on the progression of coronary calcium and of coronary artery disease assessed by repeated cardiac computed tomography scans

Abstract: BackgroundIt is not clear how severe metabolic syndrome (MS) affects the development of coronary atherosclerosis.MethodsThis was an observational, retrospective cohort study with Koreans who received health check-ups voluntarily. A total of 2426 subjects had baseline and follow-up coronary artery calcium score (CACS) data. Among them, 1079 had coronary computed tomography angiography (CCTA) data. We compared baseline CACS and any progression in subjects with and without MS. A more detailed analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…However, 5 cross-sectional studies suggested a slight increase in subclinical atherosclerosis among those with MHO, which suggests that with a longer follow-up and larger sample size a small increased risk might be identified even for metabolically healthy obesity. A study looking at progression of plaque with coronary CTA reported that MetS was an independent predictor of progression of coronary artery stenosis or development of vulnerable plaque after accounting for traditional CM risk factors including BMI, HR = 1.47, (95% CI 1.01–2.15, p = 0.045) [38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, 5 cross-sectional studies suggested a slight increase in subclinical atherosclerosis among those with MHO, which suggests that with a longer follow-up and larger sample size a small increased risk might be identified even for metabolically healthy obesity. A study looking at progression of plaque with coronary CTA reported that MetS was an independent predictor of progression of coronary artery stenosis or development of vulnerable plaque after accounting for traditional CM risk factors including BMI, HR = 1.47, (95% CI 1.01–2.15, p = 0.045) [38]. …”
Section: Discussionmentioning
confidence: 99%
“…During follow-up the proportion of MACEs in patients with metabolic syndrome was significantly increased, and multiple regression analysis still indicated that metabolic syndrome was a risk factor for MACEs after adjustment for the relevant risk factors. This indicates that the calcification score of patients with metabolic syndrome progresses rapidly and is an independent risk factor for the progression of high-risk vulnerable coronary plaques [31]. Metabolic syndrome also increases the risk of coronary atherosclerosis in postmenopausal women through arterial stiffness [32].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the effect of beam hardening on the coronary artery calcium (CAC) signal, we varied the adipose layer thickness in the stylized phantom with AEC exposures and calculated the CAC contrast, DI CAC , in the DECC image as given in Eq. (14).…”
Section: C1 Exp1: Beam Hardeningmentioning
confidence: 99%
“…(Defined ASCVD events do not include peripheral artery disease, heart failure, revascularization, and other atherosclerosis‐related, life‐altering events.) Calcium score can play a particular role for high risk groups having diabetes, rheumatoid arthritis, HIV, etc . Despite great enthusiasm among many physicians for CT coronary calcium score, there is little support for population screening due to its costs (both patient charges and radiation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation